Processing and Utilization of Tempe Liquid Waste to be Organic Fertilizer - Okki Putra P; Wahyu Nursantoso; Fajar Adi N; Sigit Yunanda (Kontribusia : Research Dissemination for Community Development, 2018)
The activities of KKN-Tematik program of Industrial Engineering Department conducted in Dukunanyar Village, Dukun Sub-district of Gresik Regency is to provide knowledge and implementation to Small and Medium Industry (IKM) tempe how to manage and utilize tempe liquid waste so as not to pollute the environment. Processing of tempe liquid waste using Adsorbtion method and filtering its function to neutralize liquid waste of tempe. Adsorption is a process of separating water from impurities by absorption of impurities such as fine particles, dissolved cations or odors contained in wastewater. The media used are zeloid stone, activated carbon and charcoal husk. Filtering is the process of irrigation or purification of water to produce clean water, free of odors, organic materials and inorganic materials contained therein. The media used are fibers, sand, and krikil. In addition to processing liquid waste tempe with adsorption method and filtering of liquid waste tempe can be utilized as Liquid Fertilizer Productive (PCP). Productive Liquid Fertilizer (PCP) is a way of utilizing tempe liquid waste with highorganic content to improve soil chemical properties to be better so that the productivity of the plant has increased. For materials used in the manufacture of Liquid Fertilizer is liquid waste tempe and fluid starter EM4. By using appropriate tools for liquid waste processing and utilization of tempe liquid waste into a productive Liquid Fertilizer (PCP) on an ongoing basis can create the integration of appropriate waste treatment, and environmentally friendly